2023
DOI: 10.3390/molecules28041805
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Based Nanomaterials for Catalytic Wastewater Treatment: A Review

Abstract: Carbon-based nanomaterials (CBM) have shown great potential for various environmental applications because of their physical and chemical properties. The unique hybridization properties of CBMs allow for the tailored manipulation of their structures and morphologies. However, owing to poor solar light absorption, and the rapid recombination of photogenerated electron-hole pairs, pristine carbon materials typically have unsatisfactory photocatalytic performances and practical applications. The main challenge in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 124 publications
0
6
0
Order By: Relevance
“…14) or ZnO 15 are widely used for antibacterial applications, although recently, carbon-based structures that can be activated with a range of wavelengths were reported. 16,17 Although inorganic materials have traditionally been more extensively explored as stimuli-activated systems, organic composites based on conductive polymers are gaining traction as they offer more flexibility in terms of biodegradation, manufacturing, and tunability of irradiation wavelength. 18 However, the major obstacle in the use of light for NP activation is the limited depth of light penetration, 19 which confines their application to thin surface coatings or surface-exposed areas of wounds.…”
Section: Introductionmentioning
confidence: 99%
“…14) or ZnO 15 are widely used for antibacterial applications, although recently, carbon-based structures that can be activated with a range of wavelengths were reported. 16,17 Although inorganic materials have traditionally been more extensively explored as stimuli-activated systems, organic composites based on conductive polymers are gaining traction as they offer more flexibility in terms of biodegradation, manufacturing, and tunability of irradiation wavelength. 18 However, the major obstacle in the use of light for NP activation is the limited depth of light penetration, 19 which confines their application to thin surface coatings or surface-exposed areas of wounds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, composite materials with a high specific surface area and grafted SFG can act as highly effective sorbents, but the difficulties of separating the solid and liquid phases limit their practical application. Despite the obvious progress in this area over the past decade, the search for highly effective means and methods of purification of water resources contaminated with TM ions is relevant [ 11 , 12 , 13 , 14 , 15 ]. Recent studies by a number of authors have focused on the development of composite materials as sorbents that combine the “desired” properties (such as the presence of SFG, developed specific surface area, mechanical strength, chemical resistance, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported significant improvement in using carbon allotropes as photocatalyst support materials. [25][26][27] Activated carbon, carbon nanofiber, carbon nanotubes, carbon spheres, carbon quantum dots, fullerene, and graphene have received significant attention. [28][29][30][31][32] Thus, combining TiO 2 and carbon can be an attractive strategy for boosting photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon is an environmentally benign raw material that is inexpensive from a manufacturing standpoint and exhibits more stability than other materials. Several studies have reported significant improvement in using carbon allotropes as photocatalyst support materials [25–27] . Activated carbon, carbon nanofiber, carbon nanotubes, carbon spheres, carbon quantum dots, fullerene, and graphene have received significant attention [28–32] .…”
Section: Introductionmentioning
confidence: 99%